2015
DOI: 10.1631/jzus.b1400343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells

Abstract: Abstract:We studied the effects of alfalfa saponin extract (ASE) on low density lipoprotein receptor (Ldlr), liver X receptor α (LXRα), and farnesoid X receptor (FXR) in normal and hyperlipidemic Buffalo rat liver (BRL) cells. Normal and hyperlipidemic BRL cells were divided into eight groups: normal, or normal cells treated with 50, 100, and 150 mg/L ASE, hyperlipidemic, or hyperlipidemic cells treated with 50, 100, and 150 mg/L ASE. After treatment for 24 h, Ldlr, LXRα, and FXR mRNA expression levels were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…ISSN online 2007-9621 López-López, P., Santos-Ricalde, R., Sarmiento-Franco, L., Sandoval-Castro, C., Segura-Correa, J., Borges-Argaez; R., Cáceres-Farfán, M., & Cetina-Montejo, L. Effect of an ethanolic extract from Enterolobium cyclocarpum pods on feed intake, egg production, and plasma lipid profile of laying hens | 1-8 reduction in plasma cholesterol using saponins from Ilex latifoli was reported (Feng et al, 2015). Studies carried out on alfalfa showed that saponin extract regulates expression of genes involved in cholesterol metabolism (Fan et al, 2018;Liang et al, 2015). Probably, the increase of HDL proportional to total cholesterol, in laying hens fed diets supplemented 120 mg/kg of EEEC, could have not a relevant effect on egg quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSN online 2007-9621 López-López, P., Santos-Ricalde, R., Sarmiento-Franco, L., Sandoval-Castro, C., Segura-Correa, J., Borges-Argaez; R., Cáceres-Farfán, M., & Cetina-Montejo, L. Effect of an ethanolic extract from Enterolobium cyclocarpum pods on feed intake, egg production, and plasma lipid profile of laying hens | 1-8 reduction in plasma cholesterol using saponins from Ilex latifoli was reported (Feng et al, 2015). Studies carried out on alfalfa showed that saponin extract regulates expression of genes involved in cholesterol metabolism (Fan et al, 2018;Liang et al, 2015). Probably, the increase of HDL proportional to total cholesterol, in laying hens fed diets supplemented 120 mg/kg of EEEC, could have not a relevant effect on egg quality.…”
Section: Discussionmentioning
confidence: 99%
“…saponins). Some studies have reported that saponins from Karaya (Sterculina urens) (Afrose, Hossain, Maki & Tsujii, 2010a), Yucca schidigera (Wang & Kim, 2011), Ilex latifolia (Feng et al, 2015), and Alfalfa (Medicago sativa) (Fan, Du, Zhou, Shi & Wang, 2015;Liang et al, 2015) reduce egg and blood plasma cholesterol, and they regulate the expression of genes associated to cholesterol metabolism. According to many of these studies, there is a close relationship between plasma and egg cholesterol in laying hens, because egg cholesterol decreases as plasma cholesterol decreases (Afrose, Hossain, & Tsujii, 2010b;Fan et al, 2015;Lokhande et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, an alfalfa saponin extract was able to upregulate the expression of FASN in hepatic tissue from laying hens. The upregulation of LDLR by an alfalfa saponin extract has also been demonstrated in healthy buffalo rat liver cells [ 49 ]. These results highlight the relevance of additional bioactive compounds of saponin-rich extracts contributing to define the specific targeted lipid metabolism network.…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis of the differentially expressed proteins showed an increased abundance of proteins related to energy production, protein synthesis, and so on. Liang et al (2015) found that alfalfa saponin extract (ASE) could upregulate mRNA expression of low density lipoprotein receptor (Ldlr) and downregulate mRNA expression of liver X receptor α (LXRα) and farnesoid X receptor (FXR) in Buffalo rat liver (BRL) cells. Therefore, ASE might ameliorate hepatic steatosis by regulating genes involved in the cholesterol metabolism.…”
Section: In This Issuementioning
confidence: 99%